The Effectiveness of Marriage Dispensation Requests at the Religious Court of Palu - Rahman, Aan Asgari; Susilawati, Susi; Mubarak, Ayyub (Tadulako Social Science and Humaniora Journal, 2024)
Dispensation to marry is a dispensation granted by the Religious Court to a bride and groom who are not old enough to enter into marriage for a man and woman who have not reached 19 (nineteen) years of age. If the two prospective husband and wife are both Muslims, then both of them can apply for marriage dispensation to the Religious Court. The formulation of the problem above is how the increase in applications for dispensation of marriage after the enactment of Law Number 16 of 2019 concerning amendments to Law Number 1 of 1974 that occurred in the Palu Religious Court and what factors submitted applications for dispensation of marriage at the Palu Religious Court. The purpose of this study was to determine the increase in marriage dispensation at the Palu Religious Court and to find out what factors submitted to marriage dispensation at the Palu Religious Court. The research method used is empirical juridical. Based on the results of the study, there is an increase in marriage dispensation in the Palu Religious Court due to several factors, namely: pregnancy, fear/fear, economy, culture/custom, and arranged marriage these factors occur because there are no detailed rules on the Marriage Law regarding the reasons that can be submitted to apply for marriage dispensation, lack of public understanding of the impact of marriage dispensation, and lack of counseling from related institutions to provide comprehensive socialization to various places about the Marriage Law. Whether or not this Marriage Law is effective can also be influenced by several factors, namely: legal factors, law enforcement factors and related institutions, facilities and facilities, community factors, and cultural factors.